Jual Beli Saham Dalam Perspektif Hukum Islam - Hadiat (STAI Al-Mas'udiyah, 2022)
The concept of sharia investment is based on the principles of morality and justice which make it the basis of value, besides that the concept of sharia investment is to avoid the so-called Maisyir, Gharar and Riba. This research is a research conducted using library research, either in the form of books, notes, or reports on research results. The results of the study show, from the perspective of sharia economic law, buying and selling or investing in shares for investment purposes is permitted, because buying and selling with halal underlying shares is even recommended because it fulfills investment and asset development as one of the maqasid sharia (Hifdzul maal). While buying and selling for speculative purposes (playing shares) is not permitted.